Chromosomal location of antibiotic resistance genes in Neisseria gonorrhoeae. - Biswas, G (1976)
Transformation with purified plasmid and chromosomal deoxyribonucleic acid from a clinical isolate of Neisseria gonorrhoeae showed that each of seven loci affecting drug resistance (penA, penB, ery, str, tet, chl, and env) was chromosomal.